Formation of some heterocycles based on hydrogen cyanide - Sedlák, Miloš; Kaválek, Jaromír; Macháček, Vladimír; Štěrba, Vojeslav (Univerzita Pardubice, 1996)
Cyanogen chloride (prepared from hydrogen cyanide) has been used to prepare chlorosulfonyl isocyanate which cab be adopted as the starting material in syntheses of N-methyl-N-phenyl-sulfuric diamides whose ortho derivates are cyclized to give substituted (1H)-2,1,3-benzothiadiazin-4(3H)-one-2,2-dioxides. Nucleophilic substitution of cyanogen chloride with sodium benzenesulfinate produces benzenesulfonyl cyanide – the starting material for production of substituted 1,2,4-oxadiazoles. Hydrogen cyanide itself was used in the Strecker synthesis of aminonitriles which served for preparation of substituted imidazolines. The nucleophilic substitution of benzoyl chloride and potassium thiocyanide gave benzoyl isothiocyanate which was further transformed into derivates of substituted 2-thioxo-4-quinazolones.